PSYCHOLINGUISTICS AND LANGUAGE PROCESSING - ALINA PREDA (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. The aim of this article is to trace the evolution of the most important theoretical and experimental approaches to language processing, from the early 1960s, which witnessed the emergence of psycholinguistics as a separate field of study, to the more advanced methods constituting the methodological infrastructure of current research in the field. Combining two disciplines, namely psychology and linguistics, psycholinguistics originally attempted to identify the ways in which lexical items and syntactic rules are stored in the mind, as well as the role played by memory in the process of discourse perception and text interpretation. More recently, however, the interest has expanded not only towards issues pertaining to discourse processing, but also towards the manner in which readers' schemata based on background knowledge and readers' inferences about a text may help them create mental representations of the narrative world.